MODERASI PEMIKIRAN HUKUM ISLAM IMAM SYAFI’I - Abdul Haris Naim (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
Almost every life is always characterized by motion and dynamics.Starting from the movement and dynamics of change anddevelopment of thought with a variety of variants, always occurcontinuously without knowing the limits. Likewise in religion, theexistence of a religion will be judged to have a function for a life, ifreligion in practice opens a wide space for the demands of motionand the dynamics of life as intended. The same thing happens alsoin Islam, on the one hand it is considered a value system that isable to provide guidance and direction for human life, but on theother hand it requires dynamic space constructed from the basicsof norms that have the essence of universal truth, because in lifealways requires constant movement and change from situation tosituation and from conditions to other conditions.